Psychometric properties of the measure of achieved capabilities in homeless services - Greenwood, Ronni Michelle (2023)
Background Purposeful participation in personally meaningful life tasks, enjoyment of positive reciprocal relationships, and opportunities to realize one’s potential are growth-related aspects of a meaningful life that should be considered important dimensions of recovery from homelessness. The extent to which homeless services support individuals to achieve the capabilities they need to become who they want to be and do what they want to do is, in turn, an important indicator of their efectiveness. In this study, we developed a measure of achieved capabilities (MACHS) for use in homeless services settings, and assessed its construct and concurrent validity. Methods We analysed data collected from homeless services users at two time points in eight European countries to assess the factor structure and psychometric properties of the new measure. Participants were adults engaged with either Housing First (n=245) or treatment as usual (n=320). Results Exploratory and confrmatory factor analyses yielded a four-factor structure of the capabilities measure: community integration, optimism, safety, and self-determination. We obtained evidence for construct validity through observed correlations between achieved capabilities and recovery, working alliance and satisfaction with services. Moreover, we obtained evidence of the measure’s concurrent validity from its positive association between HF and personal recovery, which was fully mediated by achieved capabilities. Conclusions Findings demonstrate that the MACHS is a valid and reliable measure that may be used to assess the extent to which homeless services support their clients to develop capabilities needed for growth-related recovery. Implications for practice and future research directions are discussed.